Reposition of Historical Pesantren, Madrasah and Integrated Islamic School - Hardianto Hardianto (Edumaspul: Jurnal Pendidikan, 2019)
The aim of this study is describing history and development Islamic boarding schools, madrasa and integrated Islamic school. This research is descriptive-analytic literature research. Research concludes that Islam can be developing and be accepted by Indonesian society through existence an institution that pioneered by the scholars and character education that has spirit religion, development institution education experience install it recede in his journey. Proven by existence effort positive for developing institution Islamic education and shade Ministry of Education and Culture. Since the madrasa was developed together with the emergence of the Islamic reform movement in Indonesia, the madrasa curriculum has always been done the renovation. Initially, the madrasa curriculum only consisted of religious knowledge than experience innovation corresponding with demands the times. Effort massive do by the Ministry of Religion in developing Islamic education institutions. so as Ministry Education and Culture give away opportunity for Integrated Islamic School for designing curriculum education for meet National Education Standards.